Draft Annual Plan 2006-2007 Government of Jharkhand - Planning Commission (Planning Commission, 2006)
Jharkhand ""The Land of Forest"" is one of the newly established States of Indian Union carved out of the State of Bihar in November 2000. Its undulating plateau is characterized by tropical forests and tribal settlements with abundant natural resources which need to be utilized in a sustainable manner for overall development of the State.
Planning & Development Department Government of Jharkhand